Analisis Kestabilan Lereng Jalan Tambang di Area Zona 4 PT. Bintang Sumatra Pasifik di Koto Alam Kabupaten 50 Kota - Ahmat Torkis Zudri; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. The company has not yet carried out a geotechnical plan regarding the stability of the slopes in the mining area. The slope geometry planning will be used by the Bishop Simplified and Janbu Simplified methods. Data clay : Unit Wight (γ) = 19.67 kN / m3, Cohesion (c ') = 30.1 kN / m2 and inner shear angle (ϕ') = 38.06 °. The initial slope height is 11 meters and the overall slope angle is 59°. Recommended slope geometry: 1. The Bishop Simplified method FK saturated conditions of 0.996 unsafe slopes, reduction of slope angles from 59 ° to 46 ° height of 11 meters, FK 1,339 safe slopes. 2. Janbu Simplified Method saturated FK 0.955 unsafe slope condition, slope angle from 59 ° to 44 ° with 11 meters height, then FK 1.34 slope in safe condition.